John Muir - Mara, Wil. (New York : Children's Press, 2002)
Introduces the life of John Muir, the naturalist who formed the Sierra Club to help preserve the Sierra Mountains.
Includes index.
3.6
K-3
Keywords: Muir, John, -- 1838-1914 -- Juvenile literature; Naturalists -- United States -- Biography -- Juvenile literature; Conservationists -- United States -- Biography -- Juvenile literature; Muir, John, -- 1838-1914.; Naturalists; Conservationists; Muir, John, -- 1838-1914.; Naturalists -- Biography; Conservationists -- Biography